Transposon-mediated Genome Manipulations in Vertebrates - Ivics, Zoltán (2009)
Transposable elements are segments of DNA with the unique ability to move about in the genome. This inherent feature can be exploited to harness these elements as gene vectors for diverse genome manipulations. Transposon-based genetic strategies have been established in vertebrate species over the last decade, and current progress in this field indicates that transposable elements will serve as indispensable tools in the genetic toolkit of vertebrate models. In particular, transposons can be applied as vectors for somatic and germline transgenesis, and as insertional mutagens in both loss-of-function and gain-of-function forward mutagenesis screens. The major advantage of using transposons as genetic tools is that they facilitate analysis of gene function in an easy, controlled and scalable manner. Transposon-based technologies are beginning to be exploited to link sequence information to gene functions in vertebrate models. In this article, we provide an overview of transposon-based methods used in vertebrate model organisms, and highlight the most important considerations concerning genetic applications of the transposon systems.